Alterations in the steroid hormone receptor co-chaperone FKBPL are associated with male infertility: a case-control study - Barton David; Hirst David; Downes CS; Campbell Alan; Scullion Catherine; Ward Michael; Kaluskar Soniya; Crowe Hannah; Miyagawa Yasushi; De León Johanny M; McDaid Jennifer R; Lagan Kevin; et al. (BMC, 2010)
Abstract Background Male infertility is a common cause of reproductive failure in humans. In mice, targeted deletions of the genes coding for FKBP6 or FKBP52, members of the FK506 binding protein family, can result in male infertility. In the case of FKBP52, this reflects an important role in potentiating Androgen Receptor (AR) signalling in the prostate and accessory glands, but not the testis. In infertile men, no mutations of FKBP52 or FKBP6 have been found so far, but the gene for FKBP-like (FKBPL) maps to chromosome 6p21.3, an area linked to azoospermia in a group of Japanese patients. Methods To determine whether mutations in FKBPL could contribute to the azoospermic phenotype, we examined expression in mouse and human tissues by RNA array blot, RT-PCR and immunohistochemistry and sequenced the complete gene from two azoospermic patient cohorts and matching control groups. FKBPL-AR interaction was assayed using reporter constructs in vitro. Results FKBPL is strongly expressed in mouse testis, with expression upregulated at puberty. The protein is expressed in human testis in a pattern similar to FKBP52 and also enhanced AR transcriptional activity in reporter assays. We examined sixty patients from the Japanese patient group and found one inactivating mutation and one coding change, as well as a number of non-coding changes, all absent in fifty-six controls. A second, Irish patient cohort of thirty showed another two coding changes not present in thirty proven fertile controls. Conclusions Our results describe the first alterations in the gene for FKBPL in azoospermic patients and indicate a potential role in AR-mediated signalling in the testis.